A systematic method to identify modulation of transcriptional regulation via chromatin activity reveals regulatory network during mESC differentiation - Duren, Zhana (Sci Rep, 2016)
Chromatin regulators (CRs) are crucial for connecting the chromatin level and transcriptome level by modulating chromatin structures, establishing, and maintaining epigenetic modifications. We present a systematic method to identify MOdulation of transcriptional regulation via CHromatin Activity (MOCHA) from gene expression data and demonstrate its advantage in associating CRs to their chromatin localization and understand CRs’ function. We first re-construct the CRs modulation network by integrating the correlation and conditional correlation concepts. Then we quantify the chromatin activity as hidden variable in network by integrating the upstream and downstream information. We applied MOCHA to systematically explore the interplay of CRs, TFs, and target genes in mouse embryonic stem cells (ESC). As a result, MOCHA identified 420 chromatin regulators with modulation preference, including Pou5f1 and Eed. We found that BAF complex, NuRD complex, and polycomb-group proteins, regulate the delicate balance between pluripotency and differentiation by modulating key TFs including Klf4, Tcf3, and Max; NuRD complex members Mbd3 and Hdac1 may modulate Klf4 to achieve its dual functional roles in pluripotent and differentiation stages;Imprinted gene H19 and Igf2 are modulated by DNA methylation, histone acetylation, and insulator CTCF. Finally, we analyzed CR’s combinational modulation pattern by constructing a CR-CR interaction network.